A Case of Insult: Emotion, Law, and Witchcraft Accusations in a Botswana Village Customary Court. Issue 3 (1st September 2019) - Werbner, Pnina; Werbner, Richard
Abstract : Legal anthropologists have been latecomers in the debate surrounding law and emotion, a movement responding to the notion that the law is 'imbued with emotion'. As in the US and Europe, in Botswana cases of public insults are emotionally charged, and this is particularly so in witchcraft insult hearings. Akin to hate crimes, these insults threaten public peace, kinship amity, and decency. Members of a customary court mobilize an elaborate moral lexicon from everyday life in order not simply to ascertain the forensic facts, but to persuade offenders to regain their rational good sense, reach a self-conscious emotional balance, and recover spiritual calmness. The procedure culminates in a dialogue intended to restore public peace and to elicit an apology or show of regret from defendants and forgiveness from insulted plaintiffs.